Developing a Learning Module for Road Material Testing Course - Resni Rahmayani; Ahmad Rifqi Asrib; Anas Arfandi; Yusri Kamin (Universitas Negeri Yogyakarta, 2023)
Background: A learning module, which is one of the learning facilities contains material, methods, and limitations. At Universitas Negeri Makassar, especially in the Department of Civil Engineering and Planning Education, there are only limited courses that provide learning modules. This study aims to develop a learning module for Road Material Testing course in the Department of Civil Engineering and Planning Education, Faculty of Engineering, Universitas Negeri Makassar. Modules are beneficial because the self-instruction learning system in the module allows students to study independently so that learning resources do not always have to come from lecturers.Methods: This study employed the model by Puslitjaknov (2013) which is the simplified RnD design by Borg and Gall. The stages of research include the development of learning modules, analysis of data validation results, and revision of the developed products. The research instrument used was questionnaires which were given to media and material experts to assess the validity. The other instrument was used for testing students who had previously learned about Road Material Testing.Results: Based on the validation done by material and media experts, the developed module is in the Very Valid category. The results of large-scale field trials of the module with students of the Building Engineering Education study program at Universitas Negeri Makassar show that it is Very Valid (89.65%).Conclusion: The Road Material Testing learning module was developed in accordance with the Semester Lesson Plan of Road Material Testing course with four Course Learning Outcomes (CPMK), nine sub-Course Learning Outcomes of final competencies, and four learning activities. The module was developed based on the results of the validation from material and media experts. Then, based on small and large-scale trials, the module is considered easy to understand.